1997
DOI: 10.1128/jb.179.4.1143-1152.1997
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and sequence of cymA, a gene encoding a tetraheme cytochrome c required for reduction of iron(III), fumarate, and nitrate by Shewanella putrefaciens MR-1

Abstract: The cymA gene, which encodes a tetraheme cytochrome c, was cloned from Shewanella putrefaciens MR-1. This gene complemented a mutant which had a TnphoA insertion in cymA and which was deficient in the respiratory reduction of iron(III), nitrate, fumarate, and manganese(IV). The 561-bp nucleotide sequence of cymA encodes a protein of 187 amino acids with a predicted molecular mass of 20.8 kDa. No N-terminal signal sequence was readily apparent; consistent with this, a cytochrome with a size of 21 kDa was detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
277
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 269 publications
(283 citation statements)
references
References 68 publications
5
277
0
1
Order By: Relevance
“…For protein analysis, the TCA-insoluble pellets (from above) were dissolved in 0.1 M NaOH for ≥5 days at room temperature and then protein was determined by a modified Lowry method, with bovine serum albumin as the standard [43].…”
Section: Hplc Analysis Of Glutathionementioning
confidence: 99%
“…For protein analysis, the TCA-insoluble pellets (from above) were dissolved in 0.1 M NaOH for ≥5 days at room temperature and then protein was determined by a modified Lowry method, with bovine serum albumin as the standard [43].…”
Section: Hplc Analysis Of Glutathionementioning
confidence: 99%
“…Moreover, the majority of pathways are dependent on the catalysis of electron transfer into the periplasm by the menaquinol oxidase and tetraheme cytochrome CymA . Unsurprisingly, a cymA-deficient mutant shows growth deficiencies with a variety of anoxic electron acceptors (Myers and Myers, 1997). Although it was shown experimentally in vivo and in vitro that CymA can directly transfer electrons to the respiratory fumarate reductase FccA, it was suggested that a direct transfer would also be in place toward the periplasmic nitrate and nitrite reductases NapAB and NrfA, respectively (Schwalb et al, 2002;Gao et al, 2009;Schuetz et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The sequence identity values for the other subunits of the NAP-a and NAP-b isoforms are given in Table 3. Based upon experimental work with S. denitrificans (NAP-a-based system) (Brettar et al, 2002) and S. oneidensis MR-1 (NAP-b-based-system) (Cruz-Garcia et al, 2007;Myers & Myers, 1997;Schwalb et al, 2002), both NAP isoforms must be catalytically active. It may be that in species of Shewanella that contain both NAP-a and NAP-b, the NAP isoforms are differentially regulated under different environmental conditions (pH, oxygen availability, quinol pools).…”
Section: Sequence Identity Of the Subunits Of Nap-a And Nap-b In Shewmentioning
confidence: 99%
“…The nap operons of the e-proteobacteria Wolinella succinogenes (napAGHBFLD) (Kern & Simon, 2008;Simon et al, 2003) and Campylobacter jejuni (napAGHBLD) do not include the napC gene. The function of NapC in NAP in these species and in S. oneidensis MR-1, which also lacks NapC, may be met by the periplasmic c-type cytochrome homologue CymA, which is also from the NapC/NirT family (Gao et al, 2009;Murphy & Saltikov, 2007;Myers & Myers, 1997, 2000Schwalb et al, 2003). The napCMADGH operon of the d-proteobacterium Desulfovibrio desulfuricans lacks the napB gene (Marietou et al, 2005).…”
Section: Introductionmentioning
confidence: 99%